Penicillium commune metabolic profile as a promising source of antipathogenic natural products - Diblasi, Lorena (2015)
Penicillium is an important genus of ascomycetous fungi in the environment and in food and drug production. This paper aims to investigate statins and antipathogenic natural products from a Penicillium commune environmental isolate. Fractions (F1, F2, F3 and F4) were obtained from an ethyl acetate extract. Direct insertion probe/electron ionisation/ion trap detection mass spectrometry (MS and MS/MS) identified lovastatin (1) in F1, while GC-MS showed that 3-isobutylhexahydropyrrolo[1,2-a]pyrazine-1,4-dione (2) was the main constituent of F2 (49.34%). F4 presented 3 (16.38%) as an analogue of 2 and their known structures were similar to that of an autoinducer-signal. F1 produced a significant decrease in the Pseudomonas aeruginosa biofilms, which is the main cause of bacterial pathogenicity. F2 and F4 were effective against Staphylococcus aureus biofilms, but when F2 was associated with oxacillin, it showed an important activity against both bacteria. These novel results suggest that P. commune INTA1 is a new source of promising antipathogenic products.